ANALYSIS OF DAMAGES IN UNLAWFUL ACTS LAWSUITS: STUDY OF DECISION NO. 23/Pdt.G. S/2022/PN Mnd - Sri Stevani Arumi; Wardani Rizkianti (RADJA PUBLIKA, 2025)
This study analyzes the legal implications of business actors' administrative negligence in delivering vehicle registration documents (STNK), based on Decision No. 23/Pdt.GS/2022/PN Mnd. The delay caused both material and immaterial losses to the consumer, including financial burden and reputational damage. Using a normative juridical method with case and statute approaches, the study examines the applicability of Article 1365 of the Indonesian Civil Code and the Consumer Protection Law. The findings reveal a normative gap in determining immaterial compensation within small claim court mechanisms, where the judge partially granted the claim (IDR 20 million from the IDR 50 million demanded) without clear legal reasoning or proportional assessment. This suggests an absence of standardized legal parameters to measure non-material harm in consumer disputes. The study advocates for the establishment of normative guidelines and jurisprudence to assess immaterial damages fairly in simplified civil procedures. The research contributes to legal scholarship by offering a structured critique of compensation reasoning in civil litigation, highlighting the need for clearer standards in the enforcement of consumer protection.